Platelet‐derived growth factor receptor α/glial fibrillary acidic protein expressing peritumoral astrocytes associate with shorter median overall survival in glioblastoma patients. Issue 5 (26th November 2019) - Leiss, Lina; Mega, Alessandro; Olsson Bontell, Thomas; Nistér, Monica; Smits, Anja; Corvigno, Sara; Rahman, Mohummad Aminur; Enger, Per Øyvind; Miletic, Hrvoje; Östman, Arne
Abstract: The microenvironment and architecture of peritumoral tissue have been suggested to affect permissiveness for infiltration of malignant cells. Astrocytes constitute a heterogeneous population of cells and have been linked to proliferation, migration, and drug sensitivity of glioblastoma (GBM) cells. Through double‐immunohistochemical staining for platelet‐derived growth factor receptor α (PDGFRα) and glial fibrillary acidic protein (GFAP), this study explored the intercase variability among 45 human GBM samples regarding density of GFAP+ peritumoral astrocytes and a subset of GFAP+ peritumoral astrocyte‐like cells also expressing PDGFRα. Large intercase variability regarding the total peritumoral astrocyte density and the density of PDGFRα+/GFAP+ peritumoral astrocyte‐like cells was detected. DNA fluorescence in situ hybridization analyses for commonly altered genetic tumor markers supported the interpretation that these cells represented a genetically unaffected host cell subset referred to as PDGFRα+/GFAP+ peritumoral astrocytes. The presence of PDGFRα+/GFAP+ peritumoral astrocytes was significantly positively correlated to older patient age and peritumoral astrocyte density, but not to other established prognostic factors. Notably, presence of PDGFRα+/GFAP+ peritumoral astrocytes, but not peritumoral astrocyte density, was associated with significantly shorter patient overall survival. The prognostic association of PDGFRα+/GFAP+ peritumoral astrocytes was confirmed in multivariable analyses. This exploratory study thus demonstrates previously unrecognized intercase variability and prognostic significance of peritumoral abundance of a novel PDGFRα+ subset of GFAP+ astrocytes. Findings suggest clinically relevant roles of the microenvironment of peritumoral GBM tissue and encourage further characterization of the novel astrocyte subset with regard to origin, function, and potential as biomarker and drug target. Main points: An astrocyte subset associated with shorter patient survival was identified in the peritumoral area of glioblastoma. Findings suggest that this astrocyte subset can be explored as a biomarker and treatment target.